Pengaruh Infrastruktur dan Indeks Pembangunan Manusia terhadap Penyerapan Tenaga Kerja serta Implikasi Pertumbuhan Ekonomi - Fradya Randa; Lastri Anggi Fani (Jurnal Informatika Ekonomi Bisnis, 2023)
This research aims to determine the influence of infrastructure and the Human Development Index on labor absorption and its implications for economic growth in the Riau Islands. The analysis model used is Path Analysis. The data used is a time series and cross-section from 7 districts and cities from 2011 to 2021 in the Riau Islands. Research results show that the Human Development Index (HDI) positively influences labor absorption. A high HDI will produce quality and productive human resources in increasing labor absorption to increase economic output. Different findings from this research show that infrastructure has a negative effect on economic growth in the Riau Islands. It is possible that the infrastructure proxied by road transportation infrastructure in the research does not have a large economic impact on the Riau island because the transportation that is widely used in inter-island economic activities uses sea transportation which requires quite large costs.